Gender-segregated Education in Saudi Arabia: Its Impact on Social Norms the Saudi Labor Market - Baki, Roula (Education Policy Analysis Archives, 2004)
This article examines the Kingdom of Saudi Arabia's gender-segregated higher education system and how it is used to transmit the Kingdom's traditional societal expectations to the employment sector. With Saudi Arabia's current need for economic change, the education system is retarding instead of accelerating reform. A background consisting of Saudi Arabian history, governing laws, religious beliefs and women's roles is examined. I then discuss the education system's preservation goal by considering segregation, women's mobility, videoconferencing courses, and the roles of professors. I attempt to explain how the current education system fails to prepare its students for the global economy: by limiting women's access to the labor market, and by not preparing men for the realities of the global market and therefore creating the need for migrant workers. In conclusion, conserving culture is significant, but for economic change to occur, the extent of cultural conservatism and its effect on the education system need to be re-evaluated.